2018
DOI: 10.1158/2159-8290.cd-17-1134
|View full text |Cite|
|
Sign up to set email alerts
|

The Pancreatic Cancer Microbiome Promotes Oncogenesis by Induction of Innate and Adaptive Immune Suppression

Abstract: We found that the cancerous pancreas harbors a markedly more abundant microbiome compared with normal pancreas in both mice and humans, and select bacteria are differentially increased in the tumorous pancreas compared with gut. Ablation of the microbiome protects against preinvasive and invasive pancreatic ductal adenocarcinoma (PDA), whereas transfer of bacteria from PDA-bearing hosts, but not controls, reverses tumor protection. Bacterial ablation was associated with immunogenic reprogramming of the PDA tum… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

53
1,250
4
15

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 988 publications
(1,322 citation statements)
references
References 54 publications
53
1,250
4
15
Order By: Relevance
“…However, gut flora can migrate into the pancreas and may influence the pancreatic microenvironment even in subjects with an otherwise normal pancreas. 15 Gut microbiota alterations are found in pancreatic disease and may play a role in the pathogenesis of several pancreatic diseases including acute pancreatitis, chronic pancreatitis and pancreatic cancer. 14 However, there is still only limited evidence supporting a causal relationship between gut dysbiosis and pancreatic diseases.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, gut flora can migrate into the pancreas and may influence the pancreatic microenvironment even in subjects with an otherwise normal pancreas. 15 Gut microbiota alterations are found in pancreatic disease and may play a role in the pathogenesis of several pancreatic diseases including acute pancreatitis, chronic pancreatitis and pancreatic cancer. 14 However, there is still only limited evidence supporting a causal relationship between gut dysbiosis and pancreatic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…58, 59 Consistent with their role in modulating the immune response, gut bacterial profiles are recognized as influencing the immune response directed towards tumors. 15, 60 Several studies have shown that gut microbiome profiles influence the immune therapy response to checkpoint inhibitor therapy. 6163 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Intratumor host accessory cells include cancer-associated fibroblast [35], endothelial cells [36], pericytes [37], immunosuppressive immune cells (Treg, tumor- Table 1 Selected TCR-T trails against common tumor antigen for tumors. associated macrophages, tolerogenic dendritic cells, Breg, myeloid-derived suppressor cells, mast cells) [38,39]. These accessory cells create immunosuppressive TME via pathways including 1) creating and reinforcing immune checkpoints [40]; 2) secreting immune suppressive cytokines e.g.…”
Section: The Influence Of Immunosuppressive Tumor Microenvironment (Tmentioning
confidence: 99%